Inhibition of pro-inflammatory signaling in human primary macrophages by enhancing arginase-2 via target site blockers: original article - Fitzsimons, Stephen; Muñoz-San Martín, María; Nally, Frances; Dillon, Eugene; Fashina, Ifeolutembi A.; Strowitzki, Moritz; Ramió-Torrentà, Lluís; Dowling, Jennifer K.; De Santi, Chiara; McCoy, Claire E. (Molecular therapy. Nucleic Acids, 2023)
The modulation of macrophage phenotype from a pro-inflammatory to an anti-inflammatory state holds therapeutic potential in the treatment of inflammatory disease. We have previously shown that arginase-2 (Arg2), a mitochondrial enzyme, is a key regulator of the macrophage anti-inflammatory response. Here, we investigate the therapeutic potential of Arg2 enhancement via target site blockers (TSBs) in human macrophages. TSBs are locked nucleic acid antisense oligonucleotides that were specifically designed to protect specific microRNA recognition elements (MREs) in human ARG2 3′ UTR mRNA. TSBs targeting miR-155 (TSB-155) and miR-3202 (TSB-3202) MREs increased ARG2 expression in human monocyte-derived macrophages. This resulted in decreased gene expression and cytokine production of TNF-α and CCL2 and, for TSB-3202, in an increase in the anti-inflammatory macrophage marker, CD206. Proteomic analysis demonstrated that a network of pro-inflammatory responsive proteins was modulated by TSBs. In silico bioinformatic analysis predicted that TSB-3202 suppressed upstream pro-inflammatory regulators including STAT-1 while enhancing anti-inflammatory associated proteins. Proteomic data were validated by confirming increased levels of sequestosome-1 and decreased levels of phosphorylated STAT-1 and STAT-1 upon TSB treatment. In conclusion, upregulation of Arg2 by TSBs inhibits pro-inflammatory signaling and is a promising novel therapeutic strategy to modulate inflammatory signaling in human macrophages.